(untitled) (Altre Modernità, 2020)
Like many writers in the postcolonial era, Dany Laferrière, born in Haiti and exiled in Montréal, has ambiguous, sometimes even tense relations with France. Although he himself admits that he has no problem with being published by a French publisher, he refuses to measure himself against the rules of the literary institution of the Hexagon, denying any compromise with a country that for other writers will always remain their intellectual homeland. France is, therefore, absent from his literary production since Laferrière refuses to bow to the colonizer, as well as to the dictator. France is also absent from his work because he has "découvert par hasard […] que Haïti était en Amérique et non en France", which led him to the point of wishing that Haiti “se place sous la bannière américaine" rather than the French one. Nevertheless, since 2013, Dany Laferrière has occupied the chair of Hector Bianciotti in the Académie Française. He is the first Caribbean and North American writer to enter the Coupole.”